CHALLENGES, CLASSIFICATION AND COMPARATIVE STUDY OF QOS SOLUTIONS IN MANET. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
A mobile ad-hoc network (MANET) is composed of mobile nodes without any fixed infrastructure. Mobile nodes are communicating with each other over radio links. The large amount of real-time traffic involves high bandwidth and liable to congestion. Routing in MANET is a challenging task due to high mobility of nodes in a network. Quality of Service (QoS) is an important consideration in MANET. It is more difficult to guarantee QoS in MANETs than in other type of networks. To establish the routes and to secure the resources necessary to provide the QoS requires collaboration among the nodes. Therefore, QoS routing protocols face the challenge of delivering data to destinations.Â  The appropriate QoS metrics should be used, such as bandwidth utilization, delay, packet delivery ratio (PDR) and jitter for QoS based routing. This paper provides the challenges, classification and comparison of some of the QoS solutions in MANET.Â